Post-humanist food pedagogy in Margaret Atwood’s speculative fiction: The MaddAddam Trilogy - T. P. Anupama; Diana L. Anderleen (RUDN Journal of Studies in Literature and Journalism)
The multifaceted relationship between pedagogy, food and the human condition within Margaret Atwood’s MaddAddam trilogy, delving into themes of consumption, identity, and ethics from a post-humanist perspective provides rationale to this research paper. Drawing upon the concept of “post food,” which emerges from the industrial food chain’s influence on consumption patterns, the study examines how technological advancements and industrialization that reshape human interactions with food are transacted in learning. In MaddAddam , Atwood presents a post-apocalyptic narrative that highlights the intricate interplay between food, technology, and humanity’s future. The novel portrays food production and consumption as ethical choices imbued with individual agency and linked to sustainability, challenging conventional environmentalist paradigms. Furthermore, examines the significance of edibility as a means of negotiating identity, belonging, and cohabitation within the post-apocalyptic community depicted in MaddAddam . It explores how food acts as a humanizing factor amidst the post-human landscape, where remnants of the past evoke nostalgia for “real” food. Through a synthesis of these analyses, this research paper offers a comprehensive exploration of food’s role in shaping the post-human condition in Atwood’s trilogy, shedding light on the implications of technological advancement, environmental degradation, and societal transformation on human interactions with food and the broader ecosystem, framed within the context of critical food pedagogy.